Analysis of the Implementation of ATR/BPN Regulation No. 3 of 2023 concerning the Issuance of Electronic Documents - Wilfi, Vania; Amelia Sri Kusuma Dewi; Dyah Widhiawati (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
The aim of this study is to determine and analyze how the implementation of Article 14 Paragraph (2) of Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Regulation No. 3 of 2023 concerning the issuance of electronic documents related to virtual legal data research conducted at the ATR/BPN Office in Malang City is carried out, as well as the obstacles and efforts made by the BPN in Malang City in facing obstacles in legal data research. The method used in this study is a sociological approach to law, where law is viewed not merely as written rules but as a living and evolving social institution within society. The novelty of this research lies in its attempt to highlight how the implementation of virtual legal data research activities in land registration, as regulated by Ministry of Agrarian Affairs and Spatial Planning/National Land Agency Regulation No. 6 of 2018 on Systematic Land Registration (PTSL), is carried out, particularly in Malang City. The results of this study are based on the research object, which focuses on specific research variables related to the implementation of legal data research in systematic land registration in Malang City. This study seeks to examine and analyze the challenges and efforts made by the ATR/BPN Office in Malang City in implementing legal data research in systematic land registration. The concludes that the implementation of virtual legal data research in the PTSL program still faces various obstacles, such as the absence of technical guidelines, limited human resources, technical constraints, and data inconsistencies. Improvement efforts are being made through enhancing the quality of personnel, collaborating with villages, and conducting evaluations and socialization. This study recommends that the Ministry of ATR/BPN evaluate relevant regulations and promote increased legal awareness and administrative order in land matters among the public.